2018
DOI: 10.1074/mcp.ra117.000339
|View full text |Cite
|
Sign up to set email alerts
|

Acetylome Profiling Reveals Extensive Lysine Acetylation of the Fatty Acid Metabolism Pathway in the Diatom Phaeodactylum tricornutum

Abstract: Summary Nε -lysine acetylation represents a highly dynamic and reversibly regulated post-translational modification widespread in almost all organisms, and plays important roles for regulation of protein function in diverse metabolic pathways. However, little is known about the role of lysine acetylation in photosynthetic eukaryotic microalgae. We integrated proteomic approaches to comprehensively characterize the lysine acetylome in the model diatom Phaeodactylum tricornutum. In total, 2324 acetylation sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Protein samples were subjected to standard SDS-PAGE and transferred to PVDF membranes (GE, Healthcare, Pittsburgh, USA) in 25 mM Tris, 192 mM glycine, and 20% methanol. Immunoblot was performed as described in Chen et al [ 52 ] using α-ptTES1 antibody. The signals were visualized using the method of chemiluminescence detection.…”
Section: Methodsmentioning
confidence: 99%
“…Protein samples were subjected to standard SDS-PAGE and transferred to PVDF membranes (GE, Healthcare, Pittsburgh, USA) in 25 mM Tris, 192 mM glycine, and 20% methanol. Immunoblot was performed as described in Chen et al [ 52 ] using α-ptTES1 antibody. The signals were visualized using the method of chemiluminescence detection.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported a phosphoproteomic and acetylomic analysis of P. tricornutum (Chen et al, 2014(Chen et al, , 2018. However, little is known about other PTMs in P. tricornutum.…”
Section: Discovery Of Global Post-translational Modifications In P Tmentioning
confidence: 99%
“…PTMs are dynamic cellular processes that regulate diverse protein properties in all known living organisms (Ngounou Wetie et al, 2014;Battchikova et al, 2015;Chicooree et al, 2015;Schwammle et al, 2015). It is well established that many PTM events are extensively involved in metabolic pathways and stress responses in P. tricornutum (Lepetit et al, 2013;Chen et al, 2014Chen et al, , 2018Rosenwasser et al, 2014;Veluchamy et al, 2015). Here, we performed a systematic analysis of PTM events in P. tricornutum and explored their potential functions in the response to high light intensity.…”
Section: Molecular Plantmentioning
confidence: 99%
“…Of these PTM sites, lysine is the most commonly modified amino acid residue, with only a single ionic interaction formed, thus offering more functional flexibility following acetylation, methylation, or ubiquitination [3]. Of these potential modifications, lysine acetylation is one of the most common [4]. Numerous studies have reported that this modification is widespread in both eukaryotes and prokaryotes and participates in the regulation of multiple complicated metabolic pathways [5].…”
Section: Introductionmentioning
confidence: 99%